The state of the art and issues in software process tailoring - Zakaria, Noor Azura; Ibrahim, Suhaimi; Mahrin, Mohd Nazri (IEEE, 2015)
This study aims to review research works on software process tailoring in order to investigate the state of the art of the domain in terms of research activities. Based on the review, a classification of the research works was performed and issues pertaining to the domain were highlighted. Three classifications were produced that classify the research works into critical success factors, experiences and practices in a tailoring reference model and supporting tool. The issues discussed in this study are related to the framework and model, value-based tailored process, experienceware and quality of tailored process. This paper provides essential information on the software process tailoring research works to novice researchers who plan to conduct further research in this domain.